2019
DOI: 10.29405/j.bes/32100-1053729
|View full text |Cite
|
Sign up to set email alerts
|

Pencemaran Pestisida pada Sungai Batang Gadis, Mandailing Natal, Sumatera Utara

Abstract: AbstrakBackground: Sungai Batang Gadis merupakan sungai yang sangat penting sebagai penyedia air untuk mendukung kelangsungan hidup dan kegiatan perekonomian utama masyarakat, yaitu pertanian. Disepanjang pinggiran sungai Batang Gadis banyak ditemukan daerah pertanian masyarakat yang memanfaatkan irigasi dari aliran sungai Batang Gadis. Tujuan dari penelitian ini adalah untuk menentukan tingkat pencemaran pestisida di Sungai Batang Gadis Mandailing Natal. Metode : Metode survey digunakan dalam penelitian ini d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The type of pesticide that is widely used by horticultural farmers in Gisting Disctrict is organosphosphate. The highest concentration of organophosphate pesticides was found in soil samples, while the concentration of organochlorine pesticides was higher in water [25].…”
Section: Poisoning Status Rivermentioning
confidence: 90%
“…The type of pesticide that is widely used by horticultural farmers in Gisting Disctrict is organosphosphate. The highest concentration of organophosphate pesticides was found in soil samples, while the concentration of organochlorine pesticides was higher in water [25].…”
Section: Poisoning Status Rivermentioning
confidence: 90%
“…The continuous application of insecticides will encourage the occurrence of resistance and resurgence of BPH which results in a faster population increase compared to before the application of insecticides. The use of pesticides also causes environmental pollution in the soil [4,5], waters [6][7][8], disrupts the biodiversity [9,10], and interfere with human health [11][12][13][14]. The use of the same active ingredients continuously and mixing of several active ingredients is often done by farmers in controlling BPH [15].…”
Section: Introductionmentioning
confidence: 99%
“…Surface run-off can carry pesticide residues, enter water bodies, and affect non-target organisms such as microalgae, zooplankton, and fish. A study on the quality of freshwaters in Indonesia shows that pesticides have been detected in the rivers, such as endosulfan (Prabowo & Subantoro, 2012) and malathion (Atifah et al, 2019). The study indicated that river waters have the potential to be contaminated with various types of pesticides.…”
Section: Introductionmentioning
confidence: 99%